2008
DOI: 10.1509/jimk.16.2.32
|View full text |Cite
|
Sign up to set email alerts
|

Psychic Distance: Antecedents, Retail Strategy Implications, and Performance Outcomes

Abstract: The authors propose a conceptual model of the psychic distance-organizational performance relationship that incorporates organizational factors (international experience and centralization of decision making), entry strategy, and retail strategy implications. The findings suggest that when entering psychically distant markets, retailers should adopt lowcost/low-control entry strategies and adapt their retail strategy to a greater extent than in psychically close markets. However, the authors find that such str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
167
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(189 citation statements)
references
References 76 publications
8
167
2
2
Order By: Relevance
“…Our finding supports previously found arguments on the negative association between psychic distance and subsidiary performance in single emerging market countries such as China (Carlsson et al 2005). Our finding also contrasts with prior studies that have argued that cultural and psychic distance is a positive driver of MNEs' foreign affiliates' performance in other contexts, such as in the global retail industry (Evans and Mavondo 2002;Evans et al 2008) and among foreign subsidiaries in specific emerging market regions such as Central and Eastern Europe (Dikova 2009). Thus, our study, conducted in 17 emerging markets, provides alternative evidence in relation to the previously found explanations of why greater cultural distances are positively associated with subsidiary performance, and it contributes to the on-going debate on the psychic distance paradox (O'Grady and Lane 1996).…”
Section: Discussionsupporting
confidence: 79%
“…Our finding supports previously found arguments on the negative association between psychic distance and subsidiary performance in single emerging market countries such as China (Carlsson et al 2005). Our finding also contrasts with prior studies that have argued that cultural and psychic distance is a positive driver of MNEs' foreign affiliates' performance in other contexts, such as in the global retail industry (Evans and Mavondo 2002;Evans et al 2008) and among foreign subsidiaries in specific emerging market regions such as Central and Eastern Europe (Dikova 2009). Thus, our study, conducted in 17 emerging markets, provides alternative evidence in relation to the previously found explanations of why greater cultural distances are positively associated with subsidiary performance, and it contributes to the on-going debate on the psychic distance paradox (O'Grady and Lane 1996).…”
Section: Discussionsupporting
confidence: 79%
“…Pre-existing knowledge of international operations also enables subsidiaries to better utilise local market knowledge as EMNEs have built knowledge stocks and do not need to start from scratch. Equipped with knowledge accumulated through domestic learning, subsidiaries can better make sense of the newly acquired host market specific knowledge and develop strategies and adapt services and products according to local competitive behaviour and market needs (Evans, Mavondo, & Bridson, 2008). By doing so, subsidiaries can more effectively convert host market knowledge into improved performance.…”
Section: Synergistic Effectsmentioning
confidence: 99%
“…Earlier studies have demonstrated that the possession of market-specific information by the investing firm creates an understanding of the market and its characteristics such as business climate, culture, structure of the market system, and individual customers (Carlsson et al 2005;Evans et al 2008). As a consequence, local market experience eliminates factors that prevent MNE's learning about the foreign environment (Dikova 2009).…”
Section: Introductionmentioning
confidence: 99%